Left atrial myxoma : a clinical rarity in paediatrics - Bari, Abdul; Nagi, Abdul Ghaffar; Khan, Saadat; Rehman, Habib Ur (College of Physicians and Surgeons Pakistan, 1998)
Primary cardiac tumours are very rare in paediatric age group and Myxoma is the rarest among them. In young age group, the symptoms and signs are variable and can make the diagnosis difficult. We present a case of left atrial myxoma in a nine year old boy, which remained undiagnosed for many days after the onset of symptoms of congestive cardiac failure. Two dimensional Echocardiography enabled us to arrive at correct diagnosis.